Impact of subclinical hypothyroidism on infertility and other metabolic parameters in women with polycystic ovarian syndrome in South Asia - Rolin, Israt Azmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Polycystic ovary syndrome (PCOS), is a very common endocrine and metabolic disorder in premenopausal women that affects 1 in 10 women of childbearing age. According to recent studies, the prevalence of PCOS was found around 53%. Many studies showed that subclinical hypothyroidism (SCH) and PCOS share symptoms which can influence PCOS symptoms like infertility and hormonal changes. This systematic review aimed to evaluate the impact of SCH on infertility and other metabolic parameters in women with polycystic ovarian syndrome in South Asia. For this review work, after a literature search through PubMed, Cochrane, and Google Scholar, 5 relevant papers were identified for this systematic review. The publication time was limited to the most recent 10 years, from 2011 to 2022. This review considered quantitative research on PCOS and SCH and used evidence-based data to support the findings. Among the mentioned 5 studies, 3 were cross-sectional and 2 were case-control. The studies were conducted on 2 groups: the SCH-PCOS intervention group and the PCOS control group. For the quality assessment, Cochrane’s software, review manager (RevMan) was used to eliminate duplicate studies and reduce bias. The systematic review was conducted on 1468 female patients and measured anthropometric parameters in both groups. Total cholesterol, body mass index (BMI), TSH, free testosterone levels, insulin resistance and menstrual irregularities were all higher in the SCH-PCOS group compared to the PCOS group, along with a p<0.001 for each of the parameters. Usually, SCH and PCOS share symptoms. In cholesterol, BMI, TSH, free testosterone levels, insulin resistance and menstrual irregularities there are significant correlations between SCH and PCOS. So, there are some potential impacts of SCH on infertility and other metabolic parameters in women with polycystic ovarian syndrome in South Asia.